2016
DOI: 10.4103/1596-3519.188895
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function assessment in patients with end- stage renal disease in Nigeria: A single center experience

Abstract: Aim:The purpose of this comparative study was to evaluate cognitive function in end-stage renal disease (ESRD) patients in comparison with age, sex, and level of education-matched control.Materials and Methods:This is a cross-sectional study involving 80 ESRD patients receiving maintenance hemodialysis treatment and recruited conservatively at the nephrology unit of our hospital. Eighty apparently healthy control, that were matched with the patients for age, sex and education, were also recruited. Following ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Cognitive functioning in patients with ESRD has become a major concern in recent years. 1 A meta-analysis of the impact of hemodialysis and PD on cognitive function was completed showed that patients on hemodialysis had worse cognitive functioning and a higher risk of dementia than those undergoing PD. 2 Regular hemodialysis is also called maintenance hemodialysis (MHD).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive functioning in patients with ESRD has become a major concern in recent years. 1 A meta-analysis of the impact of hemodialysis and PD on cognitive function was completed showed that patients on hemodialysis had worse cognitive functioning and a higher risk of dementia than those undergoing PD. 2 Regular hemodialysis is also called maintenance hemodialysis (MHD).…”
Section: Introductionmentioning
confidence: 99%